Rekonsepsi Gugatan Citizen Law Suit sebagai Sengketa TUN dalam Perspektif Hukum Kesejahteraan - Bita Gadsia; Siti Zuliyah (Jurnal Hukum Lex Generalis, 2025)
The background to this research is that the enactment of Law No. 30 of 2014 concerning State Administration has provided space for public advocacy lawsuits, such as citizen lawsuits and class actions, to be included in the disputes in state administrative courts. This demonstrates the government's commitment to upholding citizens' rights as subjects who can participate in reviewing and controlling government policies. However, the resolution of citizen lawsuits continues to be fraught with various obstacles, one of which is the overlapping dualism of adjudicating authority between general courts and state administrative courts. Based on this description, it is important to further examine the urgency of citizen lawsuits within the framework of welfare law. The objectives of this research are: a) to explain the implementation of citizen lawsuits in general in Indonesia; b) to explain the urgency of citizen lawsuits within the framework of a welfare state. The stages of this research method are divided into three: preparation, implementation, and completion. Starting from the preparation stage during the pre-research phase, literature related to legal issues related to citizen lawsuits was collected to formulate the research problem. The second phase is the implementation phase, which continues with a literature review aimed at reconceptualizing citizen lawsuits in resolving state administrative disputes. The next step is to develop a concept by synchronizing the laws of the State Administrative Law and the State Administration Law.